2014
DOI: 10.21547/jss.256841
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin Fen ve Teknoloji Dersinde Kullandıkları Öğretim Yöntemlerin Değerlendirilmesi

Abstract: ÖzetBu çalışmanın amacı, 4 ve 5. sınıfları okutmakta olan sınıf öğretmenlerinin fen ve teknoloji dersinde kullandıkları öğretim yöntem ve tekniklere ilişkin görüşlerini belirlemektir. Çalışmaya, Mersin ilinde bulunan ilköğretim okulunda 2009-2010 öğretim yılında görev yapmakta olan 36 sınıf öğretmeni katılmıştır. Verilerin toplanmasında, araştırmacılar tarafından hazırlanan açık uçlu soru formu kullanılmıştır. Katılımcıların seçiminde kıdem yılı, cinsiyet ve mezun oldukları lisans düzeyleri göz önünde bulundur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…When the studies aimed at determining the methods and techniques used by teachers in science teaching were examined, it was observed that teachers generally used verbal activities and direct instruction method, and did not include much innovative teaching strategies in lessons. It was observed that some teachers used activities such as role playing, experimenting and educational games (Bardak & Karamustafaoğlu, 2016 ; Doğru & Aydoğdu, 2003 ; Güneş et al, 2011 ; Oyelekan et al, 2017 ; Şimşek et al, 2012 ; Taşkaya & Sürmeli, 2014 ). Studies show that the level of remembering skills acquired by students in science courses based only on the teacher's direct instruction method is poor (Kola & Langenhoven, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…When the studies aimed at determining the methods and techniques used by teachers in science teaching were examined, it was observed that teachers generally used verbal activities and direct instruction method, and did not include much innovative teaching strategies in lessons. It was observed that some teachers used activities such as role playing, experimenting and educational games (Bardak & Karamustafaoğlu, 2016 ; Doğru & Aydoğdu, 2003 ; Güneş et al, 2011 ; Oyelekan et al, 2017 ; Şimşek et al, 2012 ; Taşkaya & Sürmeli, 2014 ). Studies show that the level of remembering skills acquired by students in science courses based only on the teacher's direct instruction method is poor (Kola & Langenhoven, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that using active learning strategies in lessons helps to increase students' motivation and achieve more positive learning outcomes (Gonzalez-Gomez, et al, 2019). However, studies show that teachers are more inclined to use traditional methods (Akcay, et al, 2016;Aydede, et al, 2006;Demirkan & Saracoglu, 2016;Dogru & Aydogdu, 2003;Onen, et al, 2008;Sahin & Guven, 2016;Simsek, et al, 2012;Taskaya & Surmeli, 2014;Yildirim, 2011). It can be said that for the use of active learning methods and techniques, teachers make more effort, prepare extra materials, the application takes time and the desired results are not always achieved, the class sizes are crowded, the school infrastructure is not sufficient, there are no laboratories or there are limited opportunities, teachers prefer traditional learning methods and techniques more due to reasons such as the need to complete them until the end.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“… Programa dayalı öğretimin uygulanışı Programa dayalı öğretimde her ne kadar aktif öğrenme yöntem-tekniklerinden faydallanılması gerektiği belirtilse de uygulamada öğretmenlerin genel olarak konuyu anlatım tekniği ile işledikleri, sorucevap tekniğinden yararlandıkları, öğrencileri aktif hale getirmek için gösteri deneyleri, soru/problem çözme, etkinlik üretme gibi etkinlikler gerçekleştirdikleri belirlenmiştir (Yıldız, 2019). Benzer şekilde ülke genelinde yapılan araştırmalar öğretmenlerin geleneksel yöntemleri daha fazla kullandıklarını göstermektedir (Akçay, Akçay & Kurt, 2016;Demirkan & Saraçoğlu, 2016;Şahin & Güven, 2016;Taşkaya & Sürmeli, 2014). Bu nedenle bu grupta konunun temel kısımları araştırmacılar tarafından zenginleştirilmiş sunumlarla (slayt gösterisi ve görseller) aktarılmıştır.…”
Section: şEkil 4 İşbirlikli Deney Yönteminde Kullanılan Deneylerunclassified